Droplets as model systems for investigating 2D crystals, glasses and the growth dynamics of granular aggregates - Ono-dit-Biot, Jean-Christophe (My University, 2021)
The research presented in this thesis focusses on the experimental study of two fundamental questions: the crystal-to-glass transition and how aggregates of adhesive droplets spread on a surface. Aggregates made of lightly adhesive oil droplets are used as models for crystals or amorphous glasses. The force applied on the aggregates can be directly measured as they are compressed. A large portion of the work focusses on the crystal-to-glass transition and tries to answer the following question: how many defects are needed in a crystal for its mechanical response to be like a glass? To answer this question, the mechanical response of a perfect mono-crystal is measured. It is found that crystals deform elastically until they fail catastrophically in a single event once the force exceeds a critical value: the yield stress. The force measured during the compression of a crystal shows a well defined number of peaks which only depends on the initial geometry of the aggregate. As defects are added (the amount of disorder increased) the number of peaks in the force measurement increases rapidly before it saturates at a value obtained for model glasses. The magnitude of the force peaks also decreases as disorder is introduced. This work concludes that even a small amount of disorder in a crystal has a significant impact on its mechanical properties. In the second project, the spreading of a monodisperse aggregate of oil droplets is studied. Droplets are added one-by-one to a growing aggregate and the area covered on the interface is measured. It is found that after an initial 3D growth, the height of the aggregate saturates and the growth only happens in 2D along the horizontal direction. The growth is analogous to a puddle of liquid. In analogy with the capillary length in liquids, the ``granular capillary length" is introduced to characterize the balance between buoyancy acting on the droplets and the adhesion strength. The height of the aggregates, in the later stage of the growth, is set by this length scale. A method was developed to characterize the adhesion between two droplets, a key parameter in this experiment, as a function of the relevant experimental parameters.
Keywords: Soft-Matter; Emulsion; Crystal-to-glass; Micropipette deflection; Crystal; Glass